الحماية الدولية للعلامة التجارية المشهورة - محجوب، فهيمة (جامعة 8 ماي 1945 قالمة, 2018)
The well-known brand is of great importance for the consumer on the one hand and for its owner on the other hand, it reflects the success of the economic project by acquiring a growing customer base where there is the popularity, success and profitability that lead creating a strong economic pillar for their owners. In view of the economic importance of the well-known mark, the principles of its protection have been progressively strengthened and have strongly imposed on the international conventions relating to intellectual property by guaranteeing an enjoyment exceptionally protected in the rules established with regard to ordinary marks.
تتمتع العلامة المشهورة بأهمية بالغة بالنسبة للمستهلك من جهة وبالنسبة لأصحابها من جهة أخري فهي تعكس نجاح المشروع الاقتصادي عن طريق اكتساب زبائن أكثر أين يكون هناك رواج في المنتجات وبقدر ما يزداد زبائنه يزداد نجاحه وربحه ما يؤدى إلى خلق مركزا اقتصاديا قويا لمالكها. ونظرا لهذه الأهمية فإن مبادئ حمايتها تعززت تدريجيا وفرضت نفسها على الاتفاقيات الدولية المتعلقة بالملكية الفكرية أين أصبحت تتمتع بحماية استثنائية تختلف عن القواعد المقررة للعلامات العادية.
Keywords: العلامات التجارية -- القانون الدولي -- الحماية القانونية -- القوانين والتشريعات